Semantic Relations of the Word Betrayal in the Context of Indonesian Social and Political Life - Heru Pratikno; Lenny Nofriyani Adam; Atsani Wulansari; Aceng Ruhendi Saifullah (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The current and future appearance of a word with the same form has the potential to experience a shift in meaning. This shift in meaning cannot be separated from historical, social and political elements. A study that can reveal the meaning of a word is semantics. In this case, the word that will be the focus of discussion is the word betrayal. Therefore, the aim of this research is that the author will explore the meaning of the word betrayal which emerged from 1965 to 1965. 2023. Collecting language data in this research uses listening, recording and note-taking techniques. Thus, the appropriate method used for this research is qualitative descriptive analysis techniques. The research results show that the word betrayal has experienced a shift in meaning. The meaning of the word betrayal that emerged in 1965 is considered extreme and has a negative image in society. However, the word betrayal has now become commonplace in the world of politics and society has accepted this. So, the meaning of the word betrayal varies greatly depending on the group's point of view, historical events and modern political life.